Effects of resistance training experience on bone mineral density and stress fractures in female college athletes: A retrospective cohort study - Kobayashi, T.; Seki, S.; Liu, M.; Chiba, I.; Oguro, T.; Makino, Y.; Kobayashi, Y.; Matsumoto, H.; Hwang, I. (Sports, 2025)
This study aimed to investigate the effects of resistance training (RT) experience on bone mineral density (BMD) and stress fractures (SFs) in female collegiate athletes. Overall, 492 female athletes from 16 competitive sports were included. Sports were categorized into four groups based on exercise load. Data on sports participation, RT experience, and SF history were obtained using a questionnaire. Total body and lumbar spine BMD were measured using dual-energy X-ray absorptiometry. Athletes with RT experience in both senior high school (ages 15-18) and university (ages 18-22), as well as those with experience from junior high school (ages 12-15) through university, had significantly higher BMD than those with no RT experience or RT experience only in senior high school (p < 0.05). Logistic regression analysis revealed that athletes with RT experience had significantly lower odds ratios for SFs compared to those with no RT experience. In the adjusted model that included sport type and university year, athletes with RT experience in junior high school, senior high school, and university had a significantly lower OR for SFs compared with no RT experience (OR = 0.06, 95% CI: 0.01-0.59, p = 0.016). No significant BMD differences were found between athletes with and without SFs (p > 0.05). The study findings suggest that initiating RT in junior high school may be associated with a reduced incidence of SFs during university.